Juvenile Delinquency as a Form of Identity Crisis: Humanistic Counseling as Its Treatment (Jurnal Sosial Humaniora dan Pendidikan, 2025)
A Adolescence is a transitional period where individuals grow from childhood to maturity. The characteristic of adolescent development is experiencing changes in all aspects. The inability of adolescents to cope with all the changes within themselves leads to an identity crisis. One form of identity crisis is shown through juvenile delinquency. Therefore, the role of counselors in Guidance and Counseling is very important in addressing these issues. One of the relevant approaches in helping adolescents at school deal with juvenile delinquency as a symptom of identity crisis is the humanistic counseling approach. This research is a descriptive qualitative study using data collection techniques conducted through in-depth interviews, participant observation, and documentation. The selection of research subjects was purposive sampling. Based on the research results, humanistic counseling is effective in addressing juvenile delinquency as a form of identity crisis that emphasizes empathy, unconditional acceptance, and congruence. Techniques such as reflection, open dialogue, and the development of internal motivation help students understand inner conflicts, enhance self-awareness, and foster personal responsibility.